Curve Lines of 20th Century Japanese Toys in the Dutch East Indies - Mahathelge Ahmad Supriyanto (East Asian Review, 2026)
The influence of Japanese culture and commodities had been present in the Dutch East Indies since the mid-19th century, one of which was toys. There were many types of toy products imported from the land of the rising sun. Basically, these products did not just appear out of nowhere, but there was a causality from various events that occurred in Japan, which led to the arrival of Japanese products, especially toys. This study discusses the early arrival of Japanese diaspora in the Dutch East Indies who chose a life in trade. One of the products sold by the Japanese diaspora is toys. The development and changes in the types of toys will be described in this study. This article used a historical method in the form of a literature study consisting of various stages of research, including heuristics, criticism, interpretation, and historiography. The results of this study explain that many Japanese diasporas in the Dutch East Indies established trading businesses, starting from shops to importers. One of the main commodities of the Japanese diaspora was toys. Japanese toys had a large market in the Dutch East Indies. This situation persisted until the eve of World War II. Due to various political barriers in the country, the Japanese diaspora in the Dutch East Indies were deported to their homeland. However, after World War II, the export of Japanese toys to the international market continued to grow instead.